SOME WAYS TO DEVELOP SPEAKING SKILL OF EFL LEARNERS (World Bulletin of Social Sciences, 2023)
This article aims to look through some helpful ways to develop and improve speaking skills of English language learners`. Some real activities can be effective for them in these cases. As speaking skill is considered one basic point in language learning, given tips are considered most resulting types. Working individually and also with teachers or peers are very significant in developing speaking skills. Some features like confidence and fluency plays great role for this purpose